The Efficacy and Safety of Hepatic Artery Infusion Chemotherapy Combined with Lenvatinib and Programmed Death (PD)-1 Inhibitors for Unresectable Intrahepatic Cholangiocarcinoma: A Retrospective Study - Yingxiao Cai; Wu Wen; Yangshuo Xia; Renhua Wan (Current Oncology, 2025)
Objectives: Although systemic chemotherapy (SC) is the mainstay for treating unresectable intrahepatic cholangiocarcinoma (ICC), its efficacy is limited and it causes severe systemic side effects. This study focuses on evaluating the effectiveness and safety of hepatic arterial infusion chemotherapy (HAIC) in combination with lenvatinib plus programmed death-1 (PD-1) inhibitors (HLP), compared to SC in combination with lenvatinib plus PD-1 inhibitors (SCLP) for unresectable ICC. Methods: We analyzed patients initially diagnosed with unresectable ICC at our center between March 2021 and December 2023, classifying them into HLP and SCLP groups according to treatment regimen. This study assessed and compared overall survival (OS), progression-free survival (PFS), tumor response, and safety outcomes across the two treatment groups. Results: This study enrolled 53 subjects in total; 25 were treated with HLP and 28 with SCLP. The two groups showed well-matched baseline characteristics. The HLP group reported an extended median OS (12.8 vs. 11.0 months, p = 0.310) and a prolonged median PFS (8.8 vs. 6.4 months, p = 0.043), compared to the SCLP group. The HLP group had a better objective response rate (ORR) (52% vs. 25%, p = 0.043) and disease control rate (DCR) (96% vs. 78.6%, p = 0.104). Based on OS (p = 0.019) and PFS (p = 0.032) results, those without extrahepatic metastasis seemed to benefit more significantly from the HLP regimen than from the SCLP regimen. The HLP group experienced fewer grade 3–4 adverse events (AEs) than the SCLP group. Conclusions: The HLP regimen for unresectable ICC is an effective and safe strategy and is potentially better suited for patients without extrahepatic metastases.